Hogyan valósulhat meg az inkluzív nevelés az autizmus spektrum zavarokkal élők számára? Carrington, S., Saggers, B., Harper-Hill, K. & Whelan, M.: Supporting Students on the Autism Spectrum in Inclusive Schools – A Practical Guide to Implementing Evidence-Based Approaches. - Trixler, Bettina; Pusztafalvi, Henriette (Iskolakultúra, 2023)
Carrington, S., Saggers, B., Harper-Hill, K. & Whelan, M. (2021). Supporting Students on the Autism Spectrum in Inclusive Schools – A Practical Guide to Implementing Evidence-Based Approaches. Routledge. DOI: 10.4324/9781003049036